2017
DOI: 10.1080/19390211.2016.1267061
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Flour Substitution Modulates Glycemic Responses and Glycemic Index of Wheat Breads in Apparent Healthy Volunteers

Abstract: Different carbohydrate foods produce different glycemic responses even with little or no difference in macronutrient composition. Cassava constitutes one of the major staples in Nigeria. Four blends of cassava-wheat bread samples with 0, 10, 15, and 20% cassava flour inclusion were fed individually to groups of healthy human volunteers. Subjects were studied on separate occasions in the morning after a 10-12-hr overnight fast. Blood glucose responses were measured at intervals of 30 min over a period of 2 hr. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…They found that the formulation containing 60% cassava starch, 10% pre‐gelatinized flour (made from 70:30 cassava starch and cassava bagasse flour) and 30% amaranth flour gave a desirable quality and sensory acceptance. Okafor et al (), who worked on bread making found that cassava flour substitution of wheat flour of up to 30% did not have a significant effect on the glycemic index of bread. However, it has been debated that most the cassava varieties have high glycemic properties so its utilization in food products must be selected carefully (Astuti, Hendriyani, & Isnawati, ; Oluba, Oredokun‐Lache, & Odutuga, ).…”
Section: Resultsmentioning
confidence: 99%
“…They found that the formulation containing 60% cassava starch, 10% pre‐gelatinized flour (made from 70:30 cassava starch and cassava bagasse flour) and 30% amaranth flour gave a desirable quality and sensory acceptance. Okafor et al (), who worked on bread making found that cassava flour substitution of wheat flour of up to 30% did not have a significant effect on the glycemic index of bread. However, it has been debated that most the cassava varieties have high glycemic properties so its utilization in food products must be selected carefully (Astuti, Hendriyani, & Isnawati, ; Oluba, Oredokun‐Lache, & Odutuga, ).…”
Section: Resultsmentioning
confidence: 99%
“…A reduction of the glycemic index of about 50% is observed compared to the control wheat bread. These values are lower than the glycemic index of wholemeal bread (GI = 76), cassava flour-based bread (GI = 88.5) and orange-fleshed sweet potato flour-based bread (GI = 51.42) with 20% substitution [2] [56] [61]. Indeed, the GI values obtained could be explained by the presence of certain compounds (fiber, protein) and acidity.…”
Section: • Glycemic Responsementioning
confidence: 95%
“…White bread is largely consumed and made without additives such as milk, egg, fruits, etc. [2]. Food represents a popular and important source of carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Among the roots, the use of Manihot esculenta Crantz tubers (aipim, cassava, Euphorbiaceae) was described by all the authors. Cassava tubers are rich in special carbohydrates that release glucose slowly in the body without generating blood glucose spikes (Okafor et al 2017;Udeme et al 2015). This composition helps maintain high energy levels for longer, being useful for high performance athletes, and makes this food very suitable for management of diabetes.…”
Section: Species Cited By Other Authorsmentioning
confidence: 99%